3(x+4y)-4x=2(2x+y)
3x+12y-4x-2*(2x+y)=0
-x+12y-(4x+2y)=0
-5x+12y-2y=0
-5x+10y=0
y=0.5x
7(x-5у)+6x=3(x+4y)+27
7(x-5*(0.5x))+6x=3(x+4*(0.5x))+27
7*(x-2.5x)+6x-3*(x+4*0.5x)-27=0
7*(-1.5x)+6x-3*(x+4*0.5x)-27=0
-10.5x+6x-3*(x+4*0.5x)-27=0
-4.5x-3*(x+4*0.5x)-27=0
-4.5x-3*3x-27=0
-4.5x-9x-27=0
-13.5x-27=0
x=-27/13.5
x=-2
3(x+4y)-4x=2(2x+y)
3(-2+4y)-4*(-2)=2(2*(-2)+y)
-6+12y-4*(-2)-2*(2*(-2)+y)=0
-6+12y-(-4*2)-2*(2*(-2)+y)=0
-6+12y+8-2*(2*(-2)+y)=0
2+12y-2*(2*(-2)+y)=0
2+12y-2*(-4+y)=0
2+12y-(-8+2y)=0
2+12y+8-2y=0
10+12y-2*y=0
10+10y=0
y=-10/10
y=-1
ответ: x=-2; y=-1.
10+х-0,5х=24
0,5х=24-10
0,5х=14
х=14 :0,5
х=28
2) тоже самое
1,5х-12+8,5х=18
10х=18+12
10х=30
х=3
3) также
5х-5+8=1-3х-6
5х+3х-5+8-1+6=0
8х+8=0
8х=-8
х=-1 (решение верное, но вот проходили ли вы данные случаи не знаю)